O desvirtuamento da negociação coletiva como instrumento de melhoria da condição social do trabalhador. - Moura, Felipe da Costa Lima (2018)
According to the interpretation of art. 7 of the Constitution of the Republic, the purpose of collective bargaining is to implement better social conditions to the worker and, above all, to adapt labor contracts to the specificities found in the workplace. Currently, it is verified that the Labor Reform (Law no. 13467/17) ended up recognizing the possibility of negotiating a decrease in working conditions and its prevalence on the normative content, a fact that ended up provoking a clear social retrocession to the rights labor relations and to disorganize the constitutional interpretation of this form of autocompositive solution. This new flexibilizing rule implied in the distortion of collective bargaining as a strategic objective of Decent Work proposed by OI. Among the strategic objectives promoted by the ILO, social dialogue is enshrined in the Decent Work Agenda proposed by the ILO. For these reasons, the International Labor Organization has promoted, through its conventions and recommendations, the encouragement of collective bargaining as an instrument of social pacification, eradication of poverty and harmonization of the work environment. It occurs that, after the validity of the Labor Reform, especially with the inclusion of art. 611-A, a review was made of the collective bargaining process, from which it would be possible to make adjustments to the minimum conditions guaranteed by the infra-legal norm, even in the case of no compensation in favor of the workers. This time, the possibility of collective bargaining and its prevalence over the legislature has been a source of considerable concern and concern within the academy, notably for the consecration of a list of rights, provided for in art. 611-A, which once negotiated will prevail over the normative content. Thus, the relevance of this study is extremely relevant, while it seeks to investigate whether the Labor Reform promoted the distortion of the collective bargaining of its main purpose: the implementation of better social conditions for workers. The present study will consist of a bibliographical and legislative research, both by the deductive method, in order to answer if there is the distortion of collective bargaining.